1996
DOI: 10.1192/bjp.169.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Postnatal Depression in Mothers and Fathers

Abstract: Prevention and early treatment of depression in fathers may benefit not only themselves but also their spouses and their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
2
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(198 citation statements)
references
References 17 publications
(3 reference statements)
11
177
2
8
Order By: Relevance
“…28 In addition to the impacts on mother and child, findings have shown that there are links between women's depression and their partner's mental health. 29,30 In men, partner depression has been found to be associated with a higher probability of reporting depression, 29 and PND in men has been reported as associated with depression in their partners during pregnancy and after delivery. 30 …”
Section: Significance For Patients In Terms Of Illhealth (Burden Of Dmentioning
confidence: 98%
“…28 In addition to the impacts on mother and child, findings have shown that there are links between women's depression and their partner's mental health. 29,30 In men, partner depression has been found to be associated with a higher probability of reporting depression, 29 and PND in men has been reported as associated with depression in their partners during pregnancy and after delivery. 30 …”
Section: Significance For Patients In Terms Of Illhealth (Burden Of Dmentioning
confidence: 98%
“…As required by the defection hypothesis, PPD does correlate with low levels of social support (Areias et al 1996;Ghubash and Abou-Saleh 1997;Thorpe et al 1992;Yoshida et al 1997) and low infant viability (Ghubash and Abou-Saleh 1997;Yoshida et al 1997). Unfortunately, studies in small, kin-based societies that are most likely to resemble ancestral social environments are essentially nonexistent.…”
Section: Tests Of the Defection Hypothesis For Postpartum Depressionmentioning
confidence: 99%
“…The father's emotional state may also influence the risk for maternal postpartum mood changes. Depression 53 and high levels of expressed emotion in a woman's partner 54 have been associated with greater likelihood of maternal depression in the 6 to 12 months after delivery. Finally, cultural factors may contribute to postpartum mood disturbances.…”
Section: Mood and Anxiety Disorders During The Postpartum Period Deprmentioning
confidence: 99%